Anxiety and depression in adult outpatients with bronchiectasis: Associations with disease severity and health‐related quality of life. (19th September 2017) - Gao, Yong‐Hua; Guan, Wei‐Jie; Zhu, Ya‐Nan; Chen, Rong‐Chang; Zhang, Guo‐Jun
Abstract: Background: Anxiety and depression might frequently affect bronchiectasis patients, but data in Chinese patients, including their association with disease severity assessed with Bronchiectasis Severity Index (BSI) and FACED score, are limited. Objective: To investigate the rate, risk factors, association with disease severity and impact of anxiety and depression on health‐related quality of life (HRQoL) in adult outpatients with steady‐state bronchiectasis. Methods: This cross‐sectional study included 163 outpatients (102 females; mean age, 45.8 years) and 80 healthy subjects (47 females; mean age, 47.1 years). Demographic, clinical indices, radiology, spirometry, aetiology, sputum bacteriology, Hospital Anxiety and Depression Scales (HADS), Pittsburgh Sleep Quality Index (PSQI) and St. George's Respiratory Questionnaire (SGRQ) were assessed. Results: Patients with steady‐state bronchiectasis had a higher rate of depression (HADS‐depression >7) (30.1% vs 10.0%, P = .001) and anxiety (HADS‐anxiety >7; 39.9% vs 6.3%, P < .001) compared with healthy subjects. Notably, no significant differences in the rate of anxiety and depression were found across different disease severity, assessed with BSI and FACED score (all P > .05). In multivariate model, factors associated with anxiety included younger age (OR = 1.05), education below college graduate (OR = 4.55) and sleep disturbance (PSQI ≥ 6; OR = 2.95); whereas sleep disturbance was the sole factor associated with depression (OR = 5.98). Patients with either depression or anxiety had more markedly impaired HRQoL affecting most domains than those without. Conclusions: Anxiety and depression are common in bronchiectasis and can negatively affect HRQoL, but not related to disease severity. Prompt assessment and treatment of these mental disorders, regardless of bronchiectasis severity, are advocated and might improve HRQoL.